Alternative Medicine Guide to Chronic Fatigue, Fibromyalgia and Enironmental Illytss - Coldberg B. (Tiburon Future Medicine Publishing, 1998)
Chronic fatigue, fibromyalgia and environmental illness can be permanently reversed using non-toxic alternative medicine treatments. In this book, 26 leading physicians explain the techniques and natural substances that brought complete recovery to their patients.
Keywords: 61